Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/pssr.202100199
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Selector and Self‐Rectifying Devices for Resistive Random‐Access Memory Application

Abstract: The recent progress of selector and self-rectifying devices for resistive randomaccess memory applications is reviewed. In particular, the performance of crossbar arrays based on resistive switching (RS) devices, the sneak-path current issue, and possible solutions is discussed. The parameters and requirements of selector devices are elucidated here, and several types of selector devices, such as a transistor-assisted transistor-one resistor, unipolar one diode-one resistor, bipolar one selector-one resistor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 188 publications
(203 reference statements)
0
17
0
Order By: Relevance
“…When an external electric field is applied to the device, the Ag electrode oxidizes and produces Ag + ions (Ag → Ag + + e – ) that migrate to the Pt bottom electrode. After reaching the Pt bottom electrode, the Ag+ ions are reduced to Ag atoms and one or more broad conductive filaments are established . Furthermore, the boron vacancies are transported toward the Ag top electrode owing to their net negative charge and participate in the formation of conductive filaments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When an external electric field is applied to the device, the Ag electrode oxidizes and produces Ag + ions (Ag → Ag + + e – ) that migrate to the Pt bottom electrode. After reaching the Pt bottom electrode, the Ag+ ions are reduced to Ag atoms and one or more broad conductive filaments are established . Furthermore, the boron vacancies are transported toward the Ag top electrode owing to their net negative charge and participate in the formation of conductive filaments.…”
Section: Resultsmentioning
confidence: 99%
“…After reaching the Pt bottom electrode, the Ag+ ions are reduced to Ag atoms and one or more broad conductive filaments are established. 58 Furthermore, the boron vacancies are transported toward the Ag top electrode owing to their net negative charge 59 and participate in the formation of conductive filaments. As the applied CC is increased from 5 μA to 5 mA, the concentrated/wider conducting filaments attempted to grow in the device (Figure 4d−g).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[35] The has normally been linked with the Schottky barrier at the electrode/electrolyte interface. [36] For example, self-rectifying behavior was also reported in a Cu/Al 2 O 3 /a-Si/Ta resistive memory where the non-linearity observed on the device I-V characteristic was ascribed to the effective Schottky barrier height at the electrode/ aSi interface. [37] The self-rectifying behavior in this work could be attributed to the rectifying property of the Schottky barrier at the SiC/W interface.…”
Section: Switching Behaviormentioning
confidence: 91%
“…Because FTJs require both directions of bias for resistance state variation, only bidirectional selectors are suitable. It has been demonstrated that these selector devices successfully suppress sneak current with a high rectifying ratio (>10 5 ), which is the current ratio of LRS at the read voltage and the opposite direction of the read voltage 142–146 . However, implementing external selectors can degrade the advantages of array configuration and integration density.…”
Section: Neuromorphic Computing Systems Based On Fluorite‐structured ...mentioning
confidence: 99%